(untitled) (Economics and region, 2024)
The article examines the formation of regional economic policy in Ukraine in the context of European integration based on implementing sustainable development goals. The importance of local self-government bodies in implementing these goals and the need for strategic reforms to expand their powers are emphasized. The study highlights the problems faced by local self-government bodies during the transition to European standards and solving environmental, economic, and social issues. During the analysis, it was found that the existing regional policy does not contribute to increasing the level of implementation of the SDGs, and in modern conditions, the problem of increasing the region’s potential is becoming more and more difficult, there is a need to adjust the existing policy by European standards. It is proven that in this context, the application of a strategic approach to the regulation of the region’s development involves the introduction of an organizational mechanism that will allow to harmonization of the functions and responsibilities of local bodies with their own capabilities and available resources. The strategy is developed considering the interests of the region, its capabilities, and coordinating the needs of various groups, and classes of the population. The article analyzes the progress of the sustainable development goals achieved in the social, economic, and environmental components, and points out the aspects and areas that need improvement. A model for the formation of regional economic policy is proposed, considering the SDGs to overcome regional disparities and strengthen overall development. It was revealed that the regional economic policy needs to be adapted to European standards and should be aimed at increasing investments, supporting SMEs, promoting innovation, developing tourism, improving infrastructure and raising the level of education. The directions and tools for the formation of regional economic policy are proposed, as well as the need for monitoring the effectiveness of the principles of sustainable development implementation, which are crucial for balanced economic, social and environmental progress, is proven.